Carmen Jones - Bizet, Georges 1838-1875.; Preminger, Otto. ([USA] Carlyle Productions, released by Twentieth Century-Fox Film Corp., 1954)
An adaptation of the tragic opera Carmen into a modern American Negro musical drama. A sensuous southern factory girl deserts a young soldier after luring him away from his sweetheart, for an arrogant prize fighter.
A CinemaScope production.
Based on the musical play of the same title, with music by Georges Bizet and book and lyrics by Oscar Hammerstein, 2d.
Screenplay: Harry Kleiner ; music director: Herschel Burke Gilbert ; film editor: Louis Loeffler.
Cast: Harry Belafonte, Dorothy Dandridge, Pearl Bailey, Olga James and Joe Adams.
Keywords: Operas; Popular music; African Americans -- Drama; Military police -- Drama